2010
DOI: 10.1167/iovs.09-5003
|View full text |Cite
|
Sign up to set email alerts
|

Differential Role of Tumor Necrosis Factor (TNF)-α Receptors in the Development of Choroidal Neovascularization

Abstract: Receptor 1b promotes the recruitment of inflammatory cells to the site of injury and exacerbated pathologic angiogenesis probably by way of the Bmx/Etk-kinase-dependent pathway in the absence of receptor 1a. On the other hand, receptor 1a-dependent apoptosis in the absence of receptor 1b leads to reduced inflammatory response and CNV lesions after laser treatment. This demonstrates the potential for specific targeting of TNF-alpha receptors for future therapies of inflammation-associated choroidal neovasculari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 26 publications
1
38
0
1
Order By: Relevance
“…Compared with unlasered controls, TNF-a staining was greater in the overlying retina of laser-treated eyes and also colocalized with isolectinlabeled CECs within CNV ( Figure 1B). Similar to previous reports, 7,8 laser-induced CNV volume was significantly reduced in mice treated with intravitreal neutralizing Ab to mouse TNF-a (TNF-a Ab) compared with mice treated with intravitreal isotype IgG control (Figure 1, C and D).…”
Section: Up-regulation Of Tnf-a Is Associated With the Development Ofsupporting
confidence: 90%
See 1 more Smart Citation
“…Compared with unlasered controls, TNF-a staining was greater in the overlying retina of laser-treated eyes and also colocalized with isolectinlabeled CECs within CNV ( Figure 1B). Similar to previous reports, 7,8 laser-induced CNV volume was significantly reduced in mice treated with intravitreal neutralizing Ab to mouse TNF-a (TNF-a Ab) compared with mice treated with intravitreal isotype IgG control (Figure 1, C and D).…”
Section: Up-regulation Of Tnf-a Is Associated With the Development Ofsupporting
confidence: 90%
“…5 The inflammatory cytokine, tumor necrosis factor (TNF)-a, was found in macrophages within CNV surgically removed from patients with neovascular AMD. 6 Inhibition of TNF-a bioactivity by neutralizing antibodies 7 or by targeting TNF-a receptor 1 8 reduced the volume and leakage of laser-induced CNV in experimental models, suggesting that TNF-aemediated signaling was important in the development of CNV. 9,10 The roles of TNF-aemediated inflammation in rheumatoid arthritis, Alzheimer disease, atherosclerosis, and diabetes have been well established, 11 and activation of NF-kB by TNF-a plays a fundamental role in these chronic inflammatory diseases.…”
mentioning
confidence: 99%
“…[29][30][31] dative stress was found to activate the canonical Wnt pathway in the retinas of oxygen-induced retinopahty rats. 32 Moreover, inflammation pathways have potent cross-talks with the Wnt signaling pathway, 33 and our previous study showed that inflammation factors such as TNF-a and ICAM-1 are upregulated in the rat retina after activation of the Wnt pathway. 24 Our results demonstrate that levels of LRP6, phosphorylated LRP6, and b-catenin are significantly elevated in the eyecups of the laser-induced CNV rodent models, demonstrating activation of Wnt signaling.…”
Section: Discussionmentioning
confidence: 97%
“…TNF-a, A PROINFLAMMATORY cytokine, is highly expressed in ischemic tissue (1)(2)(3)(4)(5) and plays a critical role in ischemiainduced recovery and regeneration processes in skeletal muscle and heart tissues (6)(7)(8)(9)(10)(11)(12). TNF-a mediates activation of divergent intracellular signaling pathways through 2 of its receptors, TNFR1 (p55) and TNFR2 (p75) (13)(14)(15)(16).…”
mentioning
confidence: 99%